Century Rural Bank, Inc. strategic plan - Jandayan, Mary Rose A.; Soledad, Miguel D.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2008)
Century Rural Bank, Inc. (CRBI) remains the main financier in the Island Garden City of Samal. Founded in 1976 as the Rural Bank of Babak, Inc. (RBBI), the Bank has grown by leaps and bounds when ne management took over the old RBBI in 1989. During the recent months, CRBI, led by its current President Mr. Rodolfo P. del Rosario, has been working on yet another transformation-the realization of its first technological breakthrough, the 24hour-ATM banking. Likewise, the bank is set to open up its 4th banking unit in Peñaplata, IGACOS by the second semester of 2008. The message is thus clear: CRBI is intent on pursuing its vision of becoming the leading financial institution in the field of rural banking in the region. For the next five years (2008-2012), management has set five strategic directions: Deposit mobilization; Customer Care; Human Resource Development; Profitability and Efficiency; Corporate Social Responsibility. To realize these goals, this Strategic Plan has evolved to provide CRBI with a guide for the phased implementation of the abovementioned strategic directions over the next five years. Aided with various analytical tools in its planning process, the Market Development proposal emerged as the best possible strategic option available to CRBI. The bank can use this generic strategy as a foundation upon which to develop new businesses and new markets thereby ensuring business growth. Market Development will help CRBI?s management better understand its existing markets and enable them to craft innovative financial instruments suitable to the needs of its markets. Entry to new markets is also a possibility. CRBI then becomes even more focused and prepared to lead the rural banking industry in Southern Mindanao in the near future.
Thesis, Graduate(Master in Management)--University of the Philippines Mindanao, 2008
Keywords: Strategic plan